2017
DOI: 10.3389/fnhum.2017.00597
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Food Choice: Effects of Superior Temporal Sulcus Stimulation

Abstract: The easy availability of food has caused a shift from eating for survival to hedonic eating. Women, compared to men, have shown to respond differently to food cues in the environment on a behavioral and a neural level, in particular to energy rich (compared to low energy) foods. It has been demonstrated that the right posterior superior temporal sulcus (STS) is the only region exhibiting greater activation for high vs. low calorie food choices. In order to test for a possible causal role of STS in food choice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 100 publications
6
50
1
1
Order By: Relevance
“…Demographic predictors of giving a wrong answer were male gender, high school or lower education, and no studies in nutrition. These data support the results of univariate analysis and previously published studies [11,18,24,29,30].…”
Section: Discussionsupporting
confidence: 92%
“…Demographic predictors of giving a wrong answer were male gender, high school or lower education, and no studies in nutrition. These data support the results of univariate analysis and previously published studies [11,18,24,29,30].…”
Section: Discussionsupporting
confidence: 92%
“…Our participants' sample consists mostly of female volunteers. As genders differ in terms of appetite, taste preferences and food choices [90][91][92], it can be argued that the study reports the response to sensory stimulation from the female perspective. However, within our data sets there is no impact of gender on any of the investigated parameters.…”
Section: Plos Onementioning
confidence: 99%
“…In a study conducted in Canada, it was reported that men reported higher intakes of energy, increased energy density and a higher percentage of energy consumed from fats and a decreased score for emotional susceptibility to disinhibition compared to women (28). A food choice favouring high energy foods is likely to lead to weight gain and subsequently to overweight and obesity (29). The physiological controls for eating and energy homeostasis are purportedly different between the sexes although delineating the differences between biological and non-biological causes is difficult (30).…”
Section: Resultsmentioning
confidence: 99%